Temporal coherency of LD light measurement by use polarimetric fiber-optic strain sensor - Domański, Andrzej; Makowski, Piotr; Michalik, Łukasz; Chychłowski, Miłosz (Photonics Letters of Poland, 2009)
In this paper we present a new non-interferometric method of temporal coherency of light measurement. The method is based on application of the polarimetric fiber-optic strain sensor in which dynamics of output signal depends on degree of polarization and in the same coherency of light coupled into sensor. The method is particularly useful for measurements of light emitted by diodes for which interferometric methods are very inconvenient. Theoretical analysis of the method is based on Mueller-Stokes matrix equation modified by additional depolarization matrix. The method was tested for LD under threshold light.